LISTEN–READ–DISCUSS (LRD) STRATEGY IMPROVE READING COMPREHENSION TO NURSING STUDENTS - Asef Wildan Munfadlila (Institut Pendidikan Tapanuli Selatan, 2023)
Abstract This study sought to determine whether or not the listen-read-discuss (LRD) method can help students' reading comprehension. It was an in-class action research project. Both quantitative and qualitative data are used in the data collection. The results of the pre-test and post-test for the reading test were used to collect quantitative data. While this was happening, qualitative information was gathered from observation sheets of kids' and teachers' behavior. Tests and observation sheets were the instruments used. The outcome demonstrates that the tactic can enhance pupils' reading comprehension of report text. The difference between the students' pre-test, post-test one, and post-test two means may be seen. The mean pre-test score was 69.5 (35%), with seven students passing with the minimum passing grade. The mean post-test scores were 72.2 (60%), with twelve students passing with the minimum passing grade, and 78.25 (85%), with seventeen students passing with the minimum passing grade.